Development of architectural models of interaction of virtual communities for organizing the collective documentation process - Getmanyuk, Pavlo; Forkun, Yuriy (Technology audit and production reserves, 2019)
The object of this research is organizational methods of virtual community creation in web area. In this article were released researches of concerning types, communicative features, information behavior, distribution of possible roles among web participants of virtual communities, methods of their organizing and management. The research was identified strengths and weaknesses of all types of virtual communities with their main opportunities in the web space. Main principles of communicative peculiarities among participants from one virtual community of each organization type were given. The main problems caused by opportunities in collaboration among different web communities. It causes uncontrollable data flows, which can have influences on a content generation process. There were analyzed a positioning of different virtual communities types. It was identified all possible integrational variations among different virtual communities. This depends on positioning principle of different web communities’ types in the web area. There were proposed three main architectural paradigms of virtual community creation. The choosing of each of them depends on necessity of data flow management for improving content quality and communication safety between different participants. Each of these paradigms has some strength and weaknesses. The own web service development is the best solution for data flow isolation from other web communities and safety. Free web services contain local virtual communities, which are contains a global one. Collaboration between different virtual communities can cause unnecessary informational behavior of their participants. The interesting method is to combine proposed paradigms. According to the results, authors proposed situational methods of architectural organizing of virtual communities. Each of them has some benefits and weak sides.